The Effect of Additive (Herbal Medicine) on The Red Blood Profile in Laying Hens - Tanjung Puspa Maldini; Sugiharto Sugiharto; Isroli Isroli (Bantara Journal of Animal Science, 2019)
This research aims to determine the amount of erythrocytes, hemoglobin levels and hematocrit levels of laying hens which are given additional herbal medicine in feed by adding herbs. Jamu consists of a mixture of temulawak, lempuyang, ginger, bitter and turmeric, each in the same portion of 20%. A total of 40 laying hens aged 35 weeks are kept for one month. The experimental design uses a completely randomized design (CRD), with 4 treatments and 5 replications so that there are 20 units of experiment, each unit contains 2 chickens with additional feed, namely T0 (basal feed), T1 (basal feed plus 0.5% herbal medicine), T2 (basal feed plus 1% herbal medicine), T3 (basal feed plus 1.5% herbal medicine). Blood sampling was done at the end of the research to calculate the amount of erythrocytes, hemoglobin levels and hematocrit levels. The results showed hematocrit levels in chickens that were added additional herbs in the ration both at T1, T2 and T3 were different (P <0.05) with chickens that were not given additional herbs in the ration. The conclusion from the research conducted is the addition of herbal medicine can increase the profile of red blood in laying hens.Keywords: Blood profile, herbs, laying hens.